Combining Ability of Several Introduced and Local Chilli Pepper (Capsicum annuum L.) Genotypes and Heterosis of the Offsprings - Trias Sitaresmi; Sriani Sujiprihati; Muhamad Syukur (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
The objective of the study was to identify the combining ability of several introduced and local chilli genotypes and heterosis effects of their offsprings, as a result of the hybridisation process. This information will be used for production of hybrid varieties. The study was conducted from November 2006 to May 2007 at Tajur experimental station, Bogor, West Java, Indonesia. The fi ve parents with their ten F1 hybrids were evaluated in a randomized complete block design (RCBD) with three replications. The results showed that hybrid IPB C15 x IPB C19 had the highest fruit weight per plant, and hybrid IPB C8 x IPB C19 had the highest heterosis for this character. Hybrid IPB C8 x IPB C15 has highest number of fruits per plant and showed heterosis effects. Crosses among introduced and local genotypes resulted a high heterosis values. Additive variance of weight and number of fruits per plant were greater than the dominant variance. IPB C19 had the best general combining ability for fruit weight per plant character. Keywords: capsicum, combining ability, heterobeltiosis, heterosis